2004
DOI: 10.1002/dvdy.20120
|View full text |Cite
|
Sign up to set email alerts
|

Expression and function of integrin α4β1 and vascular cell adhesion molecule‐1 (VCAM‐1) during sympathetic innervation of the heart

Abstract: The interaction between the integrin ␣4␤1 receptor on superior cervical ganglion (SCG) neurons and vascular cell adhesion molecule-1 (VCAM-1) in cardiac tissue has been implicated in proper development of the sympathetic innervation of the heart (Wingerd et al.[2002] J Neurosci 22:10772-10780). In this study, we examined the expression and function of ␣4␤1 and VCAM-1 in developing rat SCG and heart. In vitro, the ␣4␤1-dependent neurite outgrowth on VCAM-1 decreased by approximately 50% from postnatal day 1 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…While the upregulation (observed in the microarray analysis) of five more genes also involved in neuronal and glial differentiation as well as in neuronal migration ( Ttyh1 , Vcam1 , Omg , Fgfr3, and Cdh11 ) [62], [63], [81], [82], [83], [84], [85] was not measured by qPCR, it cannot be ruled out that their higher expression in the C4 condition might also be relevant based on the high correlation between our microarray and RT-qPCR data. The proteins codified by Dscaml1 and Vcam1 fulfill roles in cell adhesion, repulsion and the formation of neuronal networks [82], [86], which supports the previously proposed role of adhesion as a critical in vivo and in vitro regulator of the maintenance and differentiation of NSCs, and of other stem cell populations [26], [63], [87], [88].…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…While the upregulation (observed in the microarray analysis) of five more genes also involved in neuronal and glial differentiation as well as in neuronal migration ( Ttyh1 , Vcam1 , Omg , Fgfr3, and Cdh11 ) [62], [63], [81], [82], [83], [84], [85] was not measured by qPCR, it cannot be ruled out that their higher expression in the C4 condition might also be relevant based on the high correlation between our microarray and RT-qPCR data. The proteins codified by Dscaml1 and Vcam1 fulfill roles in cell adhesion, repulsion and the formation of neuronal networks [82], [86], which supports the previously proposed role of adhesion as a critical in vivo and in vitro regulator of the maintenance and differentiation of NSCs, and of other stem cell populations [26], [63], [87], [88].…”
Section: Discussionmentioning
confidence: 68%
“…The proteins codified by Dscaml1 and Vcam1 fulfill roles in cell adhesion, repulsion and the formation of neuronal networks [82], [86], which supports the previously proposed role of adhesion as a critical in vivo and in vitro regulator of the maintenance and differentiation of NSCs, and of other stem cell populations [26], [63], [87], [88]. Indeed, Dscaml1 mRNA is strongly expressed in the OB, particularly in layers that contain many differentiated neurons (i.e., the mitral layer -ML-, the superficial GCL and the glomerular layer -GL-) [47] (The Allen Brain Atlas).…”
Section: Discussionmentioning
confidence: 99%
“…The superior cervical ganglion (SCG) has been suggested to be a peripheral neuroendocrine center because of the plethora of tissues that receive adrenergic input from this source (Cardinali et al ., 1981). The SCG has been shown to be an important modulator of cardiac function that relays cardioregulatory impulses from the central nervous system (CNS) to the SCG axons terminating in the heart that release noradrenaline (NA) and activate β1 adrenergic receptors causing strengthening of the heart contractions (Wingerd et al ., 2004). In addition, altered adrenergic innervation to the heart has been implicated in sudden cardiac death following myocardial infarction (Chen et al ., 2001).…”
Section: Why Are Adrenergic Nerves Arising From the Superior Cervicalmentioning
confidence: 99%
“…In addition to the importance of the SCG in the cerebrovasculature, the SCG innervates and impacts the function of many organs including the heart (29,41,61,65,66), the eye (23,53,62,64), and secretory glands, such as the pineal gland (30,31) thyroid/parathyroid and salivary glands (7,9,10,26,49). It has also been suggested that the SCG and other sympathetic neurons function as a peripheral neuroendocrine center (8,9) serving as the communication bridge between the central nervous system and the endocrine system (9,52).…”
Section: Introductionmentioning
confidence: 99%